A modified approach to metabolic rate determination for thermal comfort prediction during high metabolic rate activities. (November 2020) - Fletcher, M.J.; Glew, D.W.; Hardy, A.; Gorse, C.
Abstract: Environmental conditions in buildings are linked to the physical and mental wellbeing of occupants. Thus, it follows that the internal environment affects human performance and user experience during sport and activity. There are several indices that are used to evaluate occupant thermal comfort, the Predicted Mean Vote (PMV) index being the metric most commonly used. PMV is designed to evaluate comfort for sedentary occupants with low metabolic rates; however, PMV has also been used to evaluate comfort for individuals engaged in high metabolic rate activities, such as those common in sport facilities. This paper investigates the implication of using PMV to evaluate thermal comfort in sport facilities using empirical data recorded over 24 months in a multi-purpose sports hall in the North of England. Data are used to develop and propose methodological modifications to improve the standard PMV model prediction to account for occupants having higher metabolic rates. The paper evaluates the use of metabolic rate data from different sources including the Compendium of Physical Activities and quantifies the impact that the metabolic weighting approach has on predicted comfort. Finally, a novel method is proposed to modify PMV for use where occupants have high metabolic rates. Despite the improvements made, the findings suggest that even a modified PMV may not be able to accurately evaluate the thermal comfort of people engaged in non-sedentary activity, recommending that use of the PMV index is restricted to activities with metabolic rates <2 MET. Highlights: PMV index lacks accuracy during high metabolic activities. Modified approach offers improvement to comfort predictions during high metabolic activities. Current use of the PMV index to evaluate comfort in sport facilities may be unreliable. Existing guidance for PMV use may require further limitation.